Ex 4.1

Ex 4.1, 1
Important
Deleted for CBSE Board 2022 Exams

Ex 4.1, 2 Deleted for CBSE Board 2022 Exams

Ex 4.1, 3 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 4 Deleted for CBSE Board 2022 Exams

Ex 4.1, 5 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 6 Deleted for CBSE Board 2022 Exams

Ex 4.1, 7 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 8 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 9 Deleted for CBSE Board 2022 Exams

Ex 4.1, 10 Deleted for CBSE Board 2022 Exams

Ex 4.1, 11 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 12 Deleted for CBSE Board 2022 Exams

Ex 4.1, 13 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 14 Deleted for CBSE Board 2022 Exams

Ex 4.1, 15 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 16 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 17 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 18 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 19 Deleted for CBSE Board 2022 Exams You are here

Ex 4.1, 20 Deleted for CBSE Board 2022 Exams

Ex 4.1, 21 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 22 Deleted for CBSE Board 2022 Exams

Ex 4.1, 23 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 24 Important Deleted for CBSE Board 2022 Exams

Last updated at Dec. 8, 2016 by Teachoo

Ex 4.1,19 Prove the following by using the principle of mathematical induction for all n ∈ N: n (n + 1) (n + 5) is a multiple of 3. Introduction If a number is multiple of 3, then it will come in table of 3 3 × 1 = 3 3 × 2 = 6 3 × 3 = 9 Any number multiple of 3 = 3 × Natural number Ex 4.1,19 Prove the following by using the principle of mathematical induction for all n ∈ N: n (n + 1) (n + 5) is a multiple of 3. Let P(n): n (n + 1) (n + 5) = 3d, where d ∈ N For n = 1 , L.H.S = 1 (1 + 1) (1 + 5) = 1.(2).(6) = 12 = (3) × 4 = R.H.S , ∴P(n) is true for n = 1 Assume P(k) is true k (k + 1) (k + 5) = 3m , where m ∈ N ((k(k + 1)) (k + 5)= 3m (k2 + k) (k + 5) = 3m k2(k + 5) + k(k + 5) = 3m k3 + 5k2 + k2 + 5k =3m k3 + 6k2 + 5k =3m We will prove that P(k + 1) is true L.H.S = (k+1) ((k+1)+1) ((k+1)+5) = (k+1) (k+2) (k+6) = ((k + 1) (k + 2)) (k + 6) = ( k(k + 2) + 1(k + 2)) (k + 6) = ( k2 + 2k + k + 2) (k + 6) = (k + 6) ( k2 + 3k +2) = k (k2 + 3k +2) + 6 (k2 + 3k +2) = k3 + 3k2 +2k + 6k2 + 6 × 3k + 6 × 2 = k3 + 3k2 +2k + 6k2 + 18k + 12 = k3 + 9k2 + 20k +12 = (3m – 6k2 – 5k ) + 9k2 + 20k +12 = 3m – 6k2 + 9k2 – 5k + 20k +12 = 3m + 3k2 + 15k + 12 = 3 (m + k2 + 5k + 4) = 3 r , where r = m + k2 + 5k +4 r is a natural number ∴ P(k + 1) is true whenever P(k) is true. ∴ By the principle of mathematical induction, P(n) is true for n, where n is a natural number